The impact of sustainable finance literacy on investment decisions - Filippini, Massimo; Leippold, Markus; Wekhof, Tobias (Journal of Banking & Finance, 2026)
This paper examines the effects of an educational program on Sustainable Finance Literacy (SFL) and its influence on sustainable investment decisions. Through a randomized controlled trial and an incentivized choice experiment, we found that our SFL program significantly improves literacy. The program also increased the probability of investing in a highly sustainable fund by 6 percentage points on the extensive margin and decreased allocations between 3.2% and 2.7% for the less sustainable funds on the intensive margin. Among participants who already held pro-sustainability attitudes, the treatment additionally led to more investments in the highly sustainable fund on the intensive margin. Higher SFL further led to more critical sustainability assessments of mid-tier funds and reduced tendencies to chase past high returns.